Economic Strategy Formulation in Recession Determination through the Role of Digital Economy - Prasanti, Noviana; retnowati, may shinta; Daniswara, Aliyya Lathifa (Journal of Sharia Economic Law, 2023)
The whole world, including Indonesia, is predicted to experience another global recession that will occur in 2023. This is supported by inflation and increases in benchmark interest rates since the end of 2022 by worldwide Central Banks simultaneously as well as food and oil and gas prices that continue to soar. In response to this, the government has entrusted the Indonesian economy to MSMEs which are considered capable of being the pillars of the country's economy, in which MSMEs have been proven to be able to survive various kinds of economic shocks such as facing a recession in previous years. This research will examine how MSME actors, especially in the Tangerang Regency area, will prepare solutions to deal with and continue to develop in the 2023 recession issue.